An Analysis of Students’ Perception of Using Grammarly as English Writing Assistant by the Tenth Grade Students of SMK Karsa Mulya Palangka Raya - Penti (Jurnal Pendidikan Dasar dan Menengah, 2025)
This study explored the perceptions of tenth-grade students at SMK Karsa Mulya Palangka Raya regarding the use of Grammarly as an English writing support tool. A descriptive quantitative design was employed, using a four-point Likert scale questionnaire adapted from O’Neill and Russell (2019). Twenty-four students participated as respondents. Descriptive statistics were used to analyze the data. Findings revealed that most students expressed positive perceptions across five indicators: the necessity of Grammarly in writing, practicality of use, self-management, motivation, and self-monitoring. However, some students required technical assistance and engaged only with basic features, suggesting limited digital literacy and incomplete understanding of the application’s potential. While Grammarly proved useful, it could not replace teachers in providing foundational grammar, punctuation, and spelling instruction. The study highlights the importance of integrating AI-based tools with pedagogical support to maximize writing skill development.